2015
DOI: 10.1038/pr.2015.153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of kidney dysfunction and angiotensinogen as an early novel biomarker of intrauterine growth restricted offspring rats

Abstract: Background: Few studies have addressed the growing concerns of chronic kidney diseases in children with intrauterine growth restriction (IUGR). Therefore, the purpose of this study was to evaluate long-term kidney dysfunction and determine if urinary angiotensinogen (AGT) was suitable as a novel early biomarker for kidney dysfunction in IUGR offspring. Methods: Pregnant rats underwent bilateral uterine artery ligation, and as a control group, sham surgeries were performed. results: The birth weight was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…; Murano et al. ). We have recently shown that transient administration of enalapril administered between 21 and 42 days of age and continuous administration of enalapril normalized the elevated urinary angiotensinogen and urinary angiotensin II (indirect markers of the intrarenal renin angiotensin II system (Kobori et al.…”
Section: Discussionmentioning
confidence: 96%
“…; Murano et al. ). We have recently shown that transient administration of enalapril administered between 21 and 42 days of age and continuous administration of enalapril normalized the elevated urinary angiotensinogen and urinary angiotensin II (indirect markers of the intrarenal renin angiotensin II system (Kobori et al.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly a study examined the effect of prenatal programming using a model of uterine artery ligation. At 32 weeks of age, programmed rats had no difference in plasma angiotensinogen compared to control rats, while, compared to controls, the programmed rats had significantly higher urinary angiotensinogen/creatinine levels at 20 and 32 weeks of age [ 45 ]. These findings are in concordance with our findings showing that prenatal programming has no effect on plasma angiotensinogen levels but causes a marked increase in urinary excretion of angiotensinogen.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of kidney dysfunction with IUGR, glomerular dysfunction has mainly been reported, and relatively few studies have been carried out on subsequent renal tubular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Brenner and Chertow suggested that the reduced number of glomeruli leads to hyperfiltration, which subsequently leads to systemic hypertension, glomerular sclerosis, and progressive deterioration of renal function . Our previous study also reported dilated diameter and sclerosis of glomeruli in IUGR rats . Including that study, however, most studies have focused on glomerular function, and limited information is available linking IUGR with renal tubular damage.…”
mentioning
confidence: 84%
See 1 more Smart Citation